Motivasi Kerja dan Gaya kepemimpinan terhadap kinerja karyawan pada PT WOM Finance - Muhajir Zikri; Fadila Fadila; Indrawan Indrawan (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aimed to analyze the influence of work motivation and leadership style on employee performance at PT WOM Finance in the Sulawesi region. Employee performance is a crucial factor in achieving organizational goals, which requires effective human resource management, including motivation and effective leadership. Methodology/approach: This study uses a quantitative approach, with questionnaires distributed to 60 employees of the company. Data were analyzed using multiple linear regression, with hypothesis testing conducted through F-tests and t-tests, as well as validity and reliability testing using SMART PLS. Results: The results of the study show that both work motivation and leadership style simultaneously have a significant influence on employee performance. Both motivation and leadership style have a positive and important influence on employee performance. Conclusions: This study concludes that work motivation and leadership style positively and significantly influence the performance of PT WOM Finance employees in the Sulawesi region. Limitations: This study had several limitations. First, it focused only on PT WOM Finance in Sulawesi, thus limiting its generalizability to other regions. Second, the use of self-reported questionnaires may introduce bias and lack qualitative depth in the data. Contribution: This study contributes to the understanding of the influence of work motivation and leadership style on employee performance in the financing sector. The results can be a reference for management to improve performance through effective motivation and leadership strategies, as well as increase the literature on HR management in Indonesia.